225 Effects of Supplementing a Live Yeast Supplement in pre-Weaning and Finishing Diets of Holstein Bull Calves on Meat Production and Quality. (21st September 2022) - Davies, Sarah J; Esposito, Giulia; Mapiye, Cletos; Villot, Clothilde; Chevaux, Eric; Raffrenato, Emiliano
Abstract: A study was conducted to evaluate the effects of a live yeast supplement in the preweaning and finishing diets of Holstein bull calves on growth performance, carcass quality attributes and physiochemical traits. Holstein bulls (n = 39) at 5 days of age were randomly allocated to one of two treatment groups with 20 receiving no yeast supplement and 19 calves receiving the yeast supplement. The inclusion level of the yeast supplement in the pre-weaning diet was 54 mg/calf/day added to the milk replacer. During the post-weaning phase, the calves in the yeast treatment group received a pelleted feed with the yeast supplement already incorporated at 150g/tonne. The bull calves were slaughtered at 156 ± 15 days and the m. longissimus thoracis et lumborum was sampled for meat quality measurements. The live yeast supplement had no significant effect (P > 0.05) on average daily gain and final body weight of Holstein bull calves. Furthermore, carcass attributes and meat physiochemical traits were not influenced (P > 0.05) by diet. It was concluded that addition of yeast to preweaning and finishing diets of dairy bull calves has no effect on meat production and quality